Analysis of Strategies in Improving the Quality of Education in the 3T Region - Valmay, Azzahra Callistadea; Supriyanto, Achmad; Sunandar, Asep (International Journal of Business, Law, and Education, 2024)
This research uses qualitative literature methods reviews. Literature review is carried out by reading various sources from international and national journals. Result of Literature review found that education in Indonesia Especially in the 3T area, the quality is still low. This research aims to gain a deeper understanding of the quality of education in the 3T region by explaining the theory in more detail regarding: Definition of 3T (Tertinggal, Terdepan dan Terluar) Region, Indicators of the Low Quality of Education in Indonesia, Procedures for Improving the Quality of Education in the 3T Region, and Strategies for Improving the Quality of Education in the 3T Region.